Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fchem.2019.00863
|View full text |Cite
|
Sign up to set email alerts
|

Layered Titanate H2Nd2Ti3O10 Intercalated With n-Butylamine: A New Highly Efficient Hybrid Photocatalyst for Hydrogen Production From Aqueous Solutions of Alcohols

Abstract: A layered perovskite-type oxide intercalated with n-butylamine is reported as an efficient photocatalyst for hydrogen production from aqueous solutions of alcohols for the first time. The hybrid photocatalyst H 2 Nd 2 Ti 3 O 10 ×BuNH 2 was synthesized by solid-state ceramic method followed by protonation, intercalation of methylamine and subsequent substitution by n-butylamine. The product was characterized by powder XRD, TGA, STA-MS, DRS, IR, and Raman spectroscopy, CHN analysis, SEM. Intercalation of n-butyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Reactions of HCN 3 ·yH 2 O with n-alkylamines lead to a series of single-phase amine derivatives with greater c parameters because of intercalation of amines into the interlayer space. In general, the c lattice parameter, which is known to correspond to the interlayer distance of the sample Kurnosenko et al, 2019), was found to be proportional to the length of the n-alkylamine chain that consists with earlier reports Jacobson et al, 1986;Tahara and Sugahara, 2003;Kurnosenko et al, 2019;Rodionov et al, 2019). Since all the samples were successfully indexed in the P4/mmm group without doubling of the c lattice parameter, we suppose that intercalation of amines did not cause a relative shift of adjacent perovskite slabs which is absent in the case of the initial protonated niobate HCN 3 ·yH 2 O.…”
Section: Characterization Of the Samplessupporting
confidence: 70%
See 4 more Smart Citations
“…Reactions of HCN 3 ·yH 2 O with n-alkylamines lead to a series of single-phase amine derivatives with greater c parameters because of intercalation of amines into the interlayer space. In general, the c lattice parameter, which is known to correspond to the interlayer distance of the sample Kurnosenko et al, 2019), was found to be proportional to the length of the n-alkylamine chain that consists with earlier reports Jacobson et al, 1986;Tahara and Sugahara, 2003;Kurnosenko et al, 2019;Rodionov et al, 2019). Since all the samples were successfully indexed in the P4/mmm group without doubling of the c lattice parameter, we suppose that intercalation of amines did not cause a relative shift of adjacent perovskite slabs which is absent in the case of the initial protonated niobate HCN 3 ·yH 2 O.…”
Section: Characterization Of the Samplessupporting
confidence: 70%
“…At the same time, stretching modes of equatorial (490, 580 cm −1 ) and located in central octahedra (765 cm −1 ) Nb-O fragments are seen not to be influenced by the amines introduction into the inorganic matrix. IR spectra (Supporting Information S2) also confirm the formation of the derivatives and point at the presence of water molecules in the interlayer space (1,625 cm −1 ) that is typical of other amine-modified compounds Kurnosenko et al, 2019;Rodionov et al, 2019) due to formation of strong hydrogen bonds. Processing of the TG curve (Rodionov et al, 2017(Rodionov et al, , 2019 corresponding to the initial protonated niobate (Figure 3) confirmed that HCN 3 ·yH 2 O does not contain residual potassium cations from the alkali precursor KCN 3 and exists in the hydrated form HCN 3 ·1.5H 2 O.…”
Section: Characterization Of the Samplesmentioning
confidence: 78%
See 3 more Smart Citations